2021
DOI: 10.3389/fimmu.2021.631044
|View full text |Cite
|
Sign up to set email alerts
|

An Immunological Perspective: What Happened to Pregnant Women After Recovering From COVID-19?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has been raging around the world since January 2020. Pregnancy places the women in a unique immune scenario which may allow severe COVID‐19 disease. In this regard, the potential unknown effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on mothers and fetuses have attracted considerable attention. There is no clear consistent evidence of the changes in the immune status of pregnant women after recovery from COVID-19. In this study, we use m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Furthermore, in a comparison of cytokine levels during pregnancy and at one-year post-partum, Graham et al (2017) found that pro-inflammatory IL-18, TNFα and MCP-1 were reduced during pregnancy while IL-10 remained unchanged. Pregnant women with COVID-19 shared similar cytokine and chemokine profiles as non-pregnant women, with the exception of eotaxin and GRO-a, while key differences between COVID-19 and healthy pregnant women have been observed in IL-12p70, MIP-1β, RANTES (Chen et al, 2021;Zhao et al, 2021). Our analysis showed that IL-18 was elevated during pregnancy regardless of disease state, which has been shown to cause TCR-independent activation of MAIT cells (Loh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in a comparison of cytokine levels during pregnancy and at one-year post-partum, Graham et al (2017) found that pro-inflammatory IL-18, TNFα and MCP-1 were reduced during pregnancy while IL-10 remained unchanged. Pregnant women with COVID-19 shared similar cytokine and chemokine profiles as non-pregnant women, with the exception of eotaxin and GRO-a, while key differences between COVID-19 and healthy pregnant women have been observed in IL-12p70, MIP-1β, RANTES (Chen et al, 2021;Zhao et al, 2021). Our analysis showed that IL-18 was elevated during pregnancy regardless of disease state, which has been shown to cause TCR-independent activation of MAIT cells (Loh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of clinical laboratory findings determined that a low white blood cell count was the only significant difference between the pregnant and nonpregnant COVID-19 immune responses (Areia and Mota-Pinto, 2020). However, pregnant or post-partum women who had recovered from COVID-19 had lower T follicular helper type 17 cells (T FH 17), memory B cells, total and 'virus'-specific (CD56 + NKP46 + ) NK cells compared to healthy pregnant women (Zhao et al, 2021). Cytokine profiles differed between healthy pregnant women and those with COVID-19 (Chen et al, 2021;Zhao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 , 23 Maternal inflammatory responses at the maternal–foetal interface, mediated through macrophages and T cells, are induced after SARS‐CoV‐2 infection, and these responses could persist for as long as 3 months after COVID‐19 recovery. 4 , 24 , 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women are a high‐risk population for severe COVID‐19 and exhibit high mortality owing to their unique immune status 21,23 . Maternal inflammatory responses at the maternal–foetal interface, mediated through macrophages and T cells, are induced after SARS‐CoV‐2 infection, and these responses could persist for as long as 3 months after COVID‐19 recovery 4,24‐26 …”
Section: Introductionmentioning
confidence: 99%